О понимании истинного и ложного в англо-американском праве - Тягло, А. В.; Tiaglo, O. V.; Тягло, О. В.; ORCID: http://orcid.org/0000-0003-0721-1153 (Форум Права. – 2019. – № 2 (55). – С. 91–99, 2019)
Компаративное исследование ряда изданий юридического словаря Блэка выявляет, что понимание истинного и ложного, истины и лжи в поле англо-американского права структурируется по разным основаниям. Во-первых, спектр понимания истинного и ложного включает бинарные оппозиции "истинное – ложное-неистинное", "истинноеправдивое – ложное-неправдивое, или лживое", "истинное-правильное – ложное-неправильное", "истинноезаконное – ложное-незаконное". Во-вторых, ложное дихотомически разделено на ложное-виновное, включая ложное-виновное-вследствие-умышленного-правонарушения и ложное-виновное-вследствие-преступной-небрежности, а также ложное-невиновное, включая непредвидимое случайно-ложное при условии соблюдения разумной осторожности и, возможно, правдивую ложь. Кроме того, в статье обосновано, что понятия истины и юридической истины находятся в отношении логического пересечения.

Comparative analysis of few editions of Black's law dictionary finds that understanding of true and false in Anglo-American law is structured for different bases. Initial basis here is nature of the reality to which characteristic of being either true or false is attributed. First of all, true and false-untrue might be understood as some characteristics of knowledge, that is, in purely cognitive sense – par excellence according to the correspondence theory of truth. The essential specificity of implementation of this theory in field of law, in general case, is that the supposed correspondence of knowledge to knowable reality does not pretend to absolute accuracy or necessity. By this reason, the knowledge found, while remaining in its nature hypothetical, or probable, acquires the status of legal truth only after and due to a court verdict in accordance with commonly accepted convention. Under this condition, not every legal truth is recognized as truth in the strict sense of the correspondence theory; and not every truth that meets requirements of the correspondence theory will be legalized by a court and recognized as legal truth. So, notions of truth and legal truth are logically intersecting. In a communication process the opposition "true-honest – false-dishonest", which characterizes, in particular, a speech act, is actualized. In situation for which consideration of some rules, norms or standards is necessary, the binary opposition "true-correct – false-incorrect" is actualized, and when the situation has special law nature – "true-lawful – false-unlawful". Essential basis to structure spectrum of understanding of false in field of law is characteristic to be in fault. False dichotomously divided into false-in-fault, including false-in-fault-by-conscious-wrong and false-in-fault-by-culpable-negligence, and false-without-in-fault, including unpredicted accidental-false after the exercise of reasonable care and, possibly, honest falsehood.

Компаративне дослідження низки видань юридичного словника Блека виявляє, що розуміння істинного й хибного, істини та хиби у полі англо-американського права структурується за різними підставами. По-перше, спектр розуміння істинного і хибного включає бінарні опозиції "істинне – хибне-неістинне", "істинне-правдиве – хибне-неправдиве, або брехливе", "істинне-правильне – хибне-неправильне", "істинне-законне – хибне-незаконне". По-друге, хибне у дихотомічний спосіб розділене на хибне-винне, включаючи хибне-винне-через-свідоме-правопорушення і хибне-виннечерез-злочинну-недбалість, а також хибне-невинне, включаючи непередбачуване випадково-хибне за умови дотримання розумної обережності та, можливо, правдиву неістину. Окрім того, у статті обґрунтовано, що поняття істини та юридичної істини знаходяться у відношенні логічного перетину.
On understanding of true and false in Anglo-American Law
Щодо розуміння істинного і хибного в англо-американському праві
Тягло, А. В. К пониманию истинного и ложного в англо-американском праве [Електронний ресурс] / А. В. Тягло // Форум Права. – 2019. – № 2 (55). – С. 91–99. –Режим доступу: http://forumprava.pp.ua/files/091-099-2019-2-FP-Tiaglo_12.pdf.
Тягло, А. В. (2019). К пониманию истинного и ложного в англо-американском праве. Форум Права, 55(2). 91–99. DOI: http://doi.org/10.5281/zenodo.3240904.
Keywords: Філософія. Логіка. Philosophy. Logic. Философия. Логика; Держава і право. State and Law. Государство и право; Філософія права. Philosophy of law. Философия права; Наукові публікації. Scientific publications. Научные публикации; истинное; ложное; истина; юридическая истина; англо-американское право; істинне; хибне; істина; юридична істина; англо-американське право; true; false; truth; legal truth; Anglo-American law